Relationship between Medication Adherence and Relapse Rate Schizophrenia Patients in the Rejotangan Health Center Area - Putri, Eva Kartika; Romadhon, Wimar Anugrah; Wulandari, Ning Arti; Suprajitno, Suprajitno (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2023)
Introduction: Relapse of schizophrenia can be caused by patients who do not adhere to medication. Patients who do not comply with taking medication can trigger the reappearance of positive and negative symptoms of schizophrenia. The purpose of this study was to analyze the relationship between medication adherence and the recurrence rate of schizophrenic patients in the working area of the Rejotangan Health Center Area.Method: This study uses a descriptive correlational research method with a cross sectional approach. Sampling using purposive sampling method with a total sample of 69 guardians of schizophrenic patients. The instruments used were the MMAS-8 questionnaire and the recurrence questionnaire. Data analysis using Spearman rho test.Results: There was a relationship between the medication adherence variable and the relapse rate of schizophrenic patients (p=0.000) and the correlation coefficient was 0.720. This result is positive, which means that there is a very strong relationship between medication adherence and the recurrence rate of schizophrenia patients in the working area of the Rejotangan Health CenterConclusions: In this case, it is hoped that the Health Service will continue to provide guidance to patients and families related to medication adherence to minimize the relapse rate of schizophrenic patients